2021
DOI: 10.1063/5.0065063
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance in ductile Ag2S-based materials via doping iodine

Abstract: Recently, a deformable and ductile inorganic semiconductor Ag2S has attracted intense attention due to its potential application in self-powered wearable and hetero-shaped electronics. However, the thermoelectric figure of merit (zT) of Ag2S is greatly limited by its extremely low carrier concentration. In this study, via doping I into Ag2S-based materials, we tune the carrier concentration into the optimal range as well as suppressing the lattice thermal conductivity. A maximum zT value of 0.26 is achieved fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Although Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 has a stable cubic structure and good plastic deformability, its thermoelectric properties are far from ideal. The carrier concentration of Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 is about 3.1 × 10 19 cm –3 at room temperature (Figure ), which is much higher than other ductile silver chalcogenides with excellent thermoelectric properties. ,,− , Due to the overhigh carrier concentration, the Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 sample has a σ as high as 1.9 × 10 5 S m –1 at room temperature (Figure a), while the room-temperature α of Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 is only −46 μV K –1 (Figure b). The resulted PF of Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 is about 4.0 μW cm –1 K –2 at 300 K (Figure S5a).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 has a stable cubic structure and good plastic deformability, its thermoelectric properties are far from ideal. The carrier concentration of Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 is about 3.1 × 10 19 cm –3 at room temperature (Figure ), which is much higher than other ductile silver chalcogenides with excellent thermoelectric properties. ,,− , Due to the overhigh carrier concentration, the Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 sample has a σ as high as 1.9 × 10 5 S m –1 at room temperature (Figure a), while the room-temperature α of Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 is only −46 μV K –1 (Figure b). The resulted PF of Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 is about 4.0 μW cm –1 K –2 at 300 K (Figure S5a).…”
Section: Resultsmentioning
confidence: 98%
“…Temperature dependence of (a) thermal conductivity (κ), (b) lattice thermal conductivity (κ L ), and (c) zT for Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 + y Se samples. (d) Comparison of zT at 300 K for cubic Ag 2 S 0.4 (Se 0.6 Te 0.4 ) 0.6 + 0.04Se with other ductile silver chalcogenides. ,,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that doping I (1 mol%), Cu (6 mol%), P (1 mol%), and Sb (5 mol%) in Ag 2 S would all result in precipitations and little change to thermoelectric performance. [ 99,100 ] Similarly, doping Ag 2 Se with various elements from IIIA, IVA, IB, and IIB groups by Conn et al. [ 22 ] also fails to tune the electrical properties.…”
Section: Ag2q Binary Thermoelectric Materialsmentioning
confidence: 99%
“…To optimize ρ and k, specific microstructure, which includes various defects with desired properties, shape, size, dimensionality and etc., is usually formed via various approaches and ways of defect engineering [2][3][4][5]. Elemental doping is one of fruitful ways that is often applied to optimally tune the transport properties and, hence, enhance thermoelectric efficiency of material [6][7][8][9][10][11][12][13][14][15]. Dopant atoms can behave as donor or acceptor centres, resulting in reducing in ρ and enhancing in the electronic contribution to k. Besides, dopant atoms are effective scattering centres for electrons and phonons, resulting in enhancing in ρ and reducing in the phonon contribution to k, respectively.…”
Section: Introductionmentioning
confidence: 99%